Inovasi Pelayanan Izin Tinggal Orang Asing Melalui Sistem Notifikasi Izin Tinggal Keimigrasian (SITITIK) - Arief Setiawan; Nina Siti Salmaniah Siregar; Budi Hartono (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The purpose of this study was to analyze and describe the innovation of foreign residence permit services carried out and to analyze the factors driving and inhibiting these innovations. The research method used is descriptive qualitative, using interview, observation, and documentation data collection techniques. The analysis uses an interactive model with the process of data reduction, data presentation, and drawing conclusions. The results show that SITITIK has met the requirements as a service innovation because it has new values and advantages over the old system; has conformity to old innovations; as new innovations experience complexity; trials have been carried out; and are easily observable. The supporting factor lies incompetent human resources while the inhibiting factor lies in the network and the presence of bugs.